PEMASARAN KENTANG DI DESA MAKAARUYEN, KECAMATAN MODOINDING - Christy Militia Linelejan; Ribka M. Kumaat; Juliana R. Mandey (AGRI-SOSIOEKONOMI, 2017)
The study aims to knowing the marketing of potatoes in Makaaruyen Village, Modoinding Sub District. The data used are primary data and secondary data. Primary data were obtained through a list of qusions that had been provided, while secondary data obtained from BP3K office Modoinding district and village office Makaaruyen Modoinding district. Sampling method is done by simple random sampling for sample of farmers and snowball sampling method for marketing agencies, where the simple is obtained based on information from the first respondent then traced to the next respondent. Data is presented in numerical form and analyzed quantitatively. The consept of measurement of variables used are costs consisting of packing, sortir fees, freight costs, loading and unloading costs, depreciation costs and retribution fees. The research result showed that there was five channel of potatoes in Makaaruyen village, Modoinding Sub District. The marketing institutions involved include village collecting, sub district collecting, sub district traders, out of town merchants and retailers. Marketing activities in the Makaaruyen Village of the Modoinding Sub District is an activity that begins with partners and cooperation between farmers and marketing agencies involved in potato marketing activities.